2020
DOI: 10.35772/ghm.2020.01010
|View full text |Cite
|
Sign up to set email alerts
|

Is single acupoint Sanyinjiao (SP 6) effective in managing insomnia? A systematic review of randomized controlled trials

Abstract: Insomnia is a symptom of physical or mental disorder and refers to decreased sleep time and potentially low quality. There is evidence showing that acupuncture could enhance management of insomnia, and Sanyinjiao (SP 6) is one of the promising acupoints. This review aimed to evaluate the effectiveness of stimulating single acupoint SP 6 in managing insomnia. The study was registered under PROSPERO CRD42019140855. English and Chinese databases were searched for randomized controlled trials on single acupoint SP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Therefore, Sanyinjiao can regulate the liver and spleen and benefit the kidney yin. It has the effects of strengthening the spleen and regulating blood, tonifying the kidney and calming the liver, dredging meridians, and activating collaterals [ 31 ]. Ba GUI is derived from the (Yellow Emperor's Canon of internal medicine).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Sanyinjiao can regulate the liver and spleen and benefit the kidney yin. It has the effects of strengthening the spleen and regulating blood, tonifying the kidney and calming the liver, dredging meridians, and activating collaterals [ 31 ]. Ba GUI is derived from the (Yellow Emperor's Canon of internal medicine).…”
Section: Discussionmentioning
confidence: 99%
“…32 A systematic review included 4 studies with 288 participants and showed that SP6 stimulation improved sleep quality, prolonged deep sleep time and prolonged rapid eye movement (REM) duration. 12 Research also showed that stimulation at SP6 improved sleep quality by increasing levels of 5-HT in the hippocampus in the rat model of insomnia. 16…”
Section: Discussionmentioning
confidence: 97%
“…Moxibustion is effective in treating mental health issues such as anxiety, depression, and insomnia. 12 , 13 , 14 Moxibustion is reported to regulate the hypothalamic-pituitary-adrenal (HPA) axis, hippocampus upregulation, and neurotransmitter synthesis for depression relief. 15 Moxibustion has been shown in studies to improve the sleep state of insomnia rats by increasing 5-hydroxytryptamine (5-HT) and 5-hydroxyindoleacetic acid levels in the hypothalamus while decreasing dopamine and norepinephrine levels.…”
Section: Introductionmentioning
confidence: 99%